Effective Public Health Strategies for Preventing Non Communicable Diseases Through Risk Factor Management and Community Based Initiatives - Effendi, Azhar; Maulana, Arfah; Dani, Dani (Journal of Asian-african Focus in Health, 2023)
Chronic non-communicable diseases (NCDs) including cardiovascular diseases, cancers, chronic respiratory diseases and diabetes are the major causes of morbidity and mortality in the world contributing close to ¾ of global mortality. As described above, NCDs are increasing progressively around the world and particularly in LMICs, with a likelihood to overwhelm the entire health sector and hinder sustainable development. This work examines evidence from numerous public health interventions aimed at preventing NCDs by controlling modifiable lifestyle factors including unhealthy diets, physical inactivity, tobacco use and excessive alcohol consumption. Both health promotion and legislative conducts have shown high levels of effectiveness: in increasing knowledge and enhancing people’s behaviors; in decreasing the opportunity of exposure to risk factors such as through tobacco taxation and through implementation of sugar-sweetened beverages taxes. Mobile programs have helped in increasing accessibility of healthy food and enhancing physical activities that would suite the decreasing incidences of obesity and related diseases. Also, under the healthcare system, screening programs and integrated care, have indeed improved early detection and control of NCDs. Nevertheless, current challenges that are related to increases in social inequalities, cultural differences, restricted access to healthcare services, etc., still remain especially in LMICs. It notes that more efforts should be channeled towards the targeted approaches in line with the geographical culture that should involve multi-sectoral participation and whose implementation should undergo periodic assessment and accreditation to increase the effectiveness of the NCD control measures. When appropriately applied, all-inclusive and work-setting informed approaches will go a long way in easing the impact of NCDs within the population and fortifying the world’s public health systems.